Relasi Sosial Masjid Baitul Falah Dengan Gereja Bethel Indonesia (GBI) Rock Di Surabaya - M Thoriqul Huda; Bisma Dwi Anggana (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
The relation between Islam and Christianity is indeed endless to study, perhaps these two religions often occur in the dynamics of inter-religious conflict. The Bethel Indonesia Rock Church and the Baitul Falah Mosque have succeeded in establishing harmonious relations which can be as an example of a form of harmony in the equality of states. The wealth of pluralism possessed in this country in fact shows that it has played a major role in building relationships that can build relationships and cooperation between religions. The Muslim-Christian network that took place by the Baitul Falah Mosque and Bethel Rock Church in Surabaya has succeeded in proving the importance of relations between religions such as Muslims and Christians. Social activities carried out together can be used as a benchmark in maintaining harmony between religious groups. Various forms of social activities can be said to be the beginning of an effort to not divide the problems that occur in the problem of religious people. In their efforts to shape these social activities, these two places of worship have indirectly established good relations with the scope of dialogue. This might happen because between GBI Rock and Baitul Falah Mosque, they participate in all activities in which they take care of each other's houses of worship without any disturbance. The two places of worship have carried out a form of life dialogue that reconciles Muslims and Christians through experiences of living together in close proximity to places. In this case, it can be understood that it is important to develop cooperation in maintaining harmony through establishing good social relations between religious communities, hence the creation of a peaceful and happy world even lives in the reality of a multi-religious society.